1996
DOI: 10.1021/ie950134z
|View full text |Cite
|
Sign up to set email alerts
|

Application of γ-ray Attenuation for Measurement of Gas Holdups and Flow Regime Transitions in Bubble Columns

Abstract: In this study a γ-ray densitometry was used to measure radial and axial volume fraction distributions in a 0.21 m diameter bubble column, and flow regime transitions in a 0.05 m and 0.21 m diameter bubble columns. Experiments were conducted with two- and three-phase systems (nitrogen−Fischer−Tropsch derived waxes−iron oxide or silica particles) in both batch and continuous modes of operation at 265 °C and ambient pressure. Average radial gas holdups in the large diameter column showed the existence of a maximu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 35 publications
2
18
0
Order By: Relevance
“…Thus, Veera et al [17] reported on the use of a ␥-ray attenuation technique to measure time-averaged radial gas distribution profiles in an aerated stirred tank from sets of chordal attenuation measurements obtained at different horizontal cross-sections. Bukur et al [18] used this technique in bubble columns. Kumar et al [19], Kemoun et al.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Veera et al [17] reported on the use of a ␥-ray attenuation technique to measure time-averaged radial gas distribution profiles in an aerated stirred tank from sets of chordal attenuation measurements obtained at different horizontal cross-sections. Bukur et al [18] used this technique in bubble columns. Kumar et al [19], Kemoun et al.…”
Section: Introductionmentioning
confidence: 99%
“…However, these results were found to clearly contradict the measurements performed by Hibiki et al 48 as well as some experimental observations. 67,68 One plausible explanation for this discrepancy could possibly be the error embedded in the turbulent dissipation rate prediction 69 as a consequence of the turbulence model being applied contributing in turn to excessively high coalescence rates in the MUSIG model. As reported in Chen et al, 39 similar observations also confirmed the high coalescence rates that were experienced in their bubble column study.…”
Section: Isothermal Bubbly Turbulent Pipe Flow Resultsmentioning
confidence: 99%
“…either gas phase true(IiSP,1true) or liquid phase true(IiSP,2true), as follows (as shown in Figure ): IiSP,j=I0eμjρjli(j=1,2) Combining Equations we get expression (6):­ ψi1=ln(IiTP)ln(IiSP,2)ln(IiSP,1)ln(IiSP,2) where IiTP is intensity measured at two‐phase operating conditions, IiSP,1 is intensity measured with pure gas phase (unity gas holdup), IiSP,2 is intensity measured with liquid phase (zero gas holdup), and ψi1 denotes the discrete chordal holdup of the gas phase at different x i . For extracting chordal‐averaged gas holdup at any x i , three measurements are required: column filled with liquid phase, column filled with gas phase (empty column), and column operating at two‐phase conditions …”
Section: Densitometry Techniquementioning
confidence: 99%